2007
DOI: 10.1007/s10815-007-9114-0
|View full text |Cite
|
Sign up to set email alerts
|

The development of novel quantification assay for mitochondrial DNA heteroplasmy aimed at preimplantation genetic diagnosis of Leigh encephalopathy

Abstract: (1) This method provides rapid and reliable PGD for Leigh encephalopathy. (2) The variable heteroplasmy with somatic mitosis was suggested. (3) T8993G mutation was existed in undeveloped embryo, and the bottleneck theory was supported. The limited heteroplasmy dispersion of blastomeres from same embryo also supported reliability of PGD for T8993G mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
1
14
0
2
Order By: Relevance
“…A previous study showed that polar bodies are effective for preimplantation genetic diagnosis (PGD) to deduce the proportion of mutated mtDNA in mouse oocytes (20). However, subsequent studies using polar bodies from human oocytes (30) and blastomeres from human embryos (31,32) indicated that blastomeres are more appropriate than are polar bodies for PGD to deduce the proportion of mutated mtDNA. Although this procedure would not completely exclude the mutated mtDNA from the affected mothers, our previous studies (33,34) showed the presence of intermitochondrial complementation to maintain normal respiratory function in the presence of the mutated mtDNA.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that polar bodies are effective for preimplantation genetic diagnosis (PGD) to deduce the proportion of mutated mtDNA in mouse oocytes (20). However, subsequent studies using polar bodies from human oocytes (30) and blastomeres from human embryos (31,32) indicated that blastomeres are more appropriate than are polar bodies for PGD to deduce the proportion of mutated mtDNA. Although this procedure would not completely exclude the mutated mtDNA from the affected mothers, our previous studies (33,34) showed the presence of intermitochondrial complementation to maintain normal respiratory function in the presence of the mutated mtDNA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the similarity of heteroplasmy levels of blastomeres within an embryo, the heteroplasmy levels among embryos varied considerably. Interestingly, the heteroplasmy levels of individual lymphocytes from a subject with a 44.3% whole blood heteroplasmy proved to be highly variable, ranging from 11% to 70% (Tajima et al 2007).…”
Section: Mitochondrial Dna Geneticsmentioning
confidence: 97%
“…Available data on human preimplantation embryos are limited and suffer from small sample size and technical limitations (Monnot et al, 2011; Steffann et al, 2006; Tajima et al, 2007) emphasizing the need to conduct thorough studies in nonhuman primate models.…”
Section: Introductionmentioning
confidence: 99%